Cigarette smoking and abdominal obesity: a meta-analysis of observational studies. (December 2013) - Shi, Lu; An, Ruopeng; Meijgaard, Jeroen Van
<x xml:space="preserve">Abstract</x> Background: Smoking and obesity are two of the leading causes of preventable death in developed countries. We conducted a meta-analysis to examine the association between cigarette smoking and abdominal obesity measured by waist-to-hip circumference ratio (WHR). Method: Keyword and reference search were conducted in four electronic bibliographic databases: Cochrane Library, Embase, MEDLINE, and Web of Science. Articles were included based on predefined study selection criteria. Random-effect model was performed to estimate the relationship between cigarette smoking and abdominal obesity. Results: Fifteen studies (116 146 subjects) met the study selection criteria and were included in the meta-analysis. Compared to those who have never smoked, current cigarette smokers who smoke in a regular basis are associated with 0.0113 (95% CI: 0.0081–0.0145, p < 0.001) higher WHR. Publication bias could be present as the sample sizes of individual studies and the effect sizes are negatively correlated (p < 0.01). Conclusions: In this meta-analysis, we found some preliminary evidence that links cigarette smoking to abdominal obesity. This study has important limitations pertained to observational study design, publication bias, and measurement error. Future research on the casual effect of smoking on abdominal obesity is warranted.